Linguistic portrait of a writer as the object ofstylistics and history ofliterary language - Myalkovska, Ludmyla (Stylistyka, 2021)
Specific of language and creativity of I. Nechui- Levytskyi’s in the context of history of Ukrainian literary language is outlined. The analysis of idiostyle writer is carried out after presence in the artistic texts of conceptual lexical units which form lexical-associative field “intelligentsia”. The basie structural and semantic types of metaphors are considered with key words dream, idea, heart, soul. Activity of comparisons and artistic definitions is marked in the system of figurative and stylistic language means of the researched prose. The last definitions are concemed such concepts, as “intelligentsia”, “nationalism”, “life”.